Semantic Analyses in Forensic Text Types - Karaman, Burcu İlkay (The Bulletin of Legal Medicine, 2017)
In recent years it has become inevitable to consult linguists in order to gain expert opinion in many forensic investigations. Forensic linguists, who are frequently faced with the analyses of forensic text types, can indeed play an important role in the solution of criminal cases, the tracking down of an offender or essentially may even contribute to the decision-making process of judges. Hence, this article deals with cases which a forensic linguist may encounter in their profession; in particular with cases which include different semantic analysis strategies to be applied in forensic text types. Specifically the case of polysemy will be dealt with, which constitutes a particular instance in relevance to lexical ambiguity and thus represents an important problem in communication. Thus, this article discusses four cases with regard to analyses to be performed in forensic text types by forensic linguists.